Segurança e criminalidade organizada - Cruz, Marco António Ferreira da (2016)
Globalization brought some deep changes to the world (dis)order. Nowadays, more than in other moment in history, we are closer to the ones physically far, living in “global village” called by Marshall McLuhan (1962). The concepts and premises built in this new order, have totally broken with the ones that “came out from Westphalia”, which had last to the end of the cold war, like, for example, the concept of security. Since then, security has been facing one of its biggest transformations ever, completely disrupting the state border based idea and starting to be extended to other domains, as human, economic, environmental and IT security, among others. In this global and interdependent environment, “new” threats and risks have raised, which are demanding a comprehensive approach from the States, international organizations and other actors, to allow the analysis and understanding its impacts on the various society sectors and orders. Inside the enormous challenges to the global security, it is important to regard the organized crime, which covers, by itself, a set of threats and risks, enhanced by its connection to other types of criminality, such as terrorism. The goals pursued and the tactics used by criminal organizations during the perpetration of illegal activities, specially the drug smuggling, have impact in an wide spectrum of the social, economic financial and politic dimensions, which should not be underestimated, otherwise our own security may be compromised. Therefore, the current investigation intends to be an important catalyst to the idea debate inside security scope, through the analysis of the organized crime and the drug smuggling, adding to a discussion of this issue, which should be deeper and holistic, aiming a better understanding of the challenges provided by our society.